2020
DOI: 10.1093/ptj/pzaa191
|View full text |Cite
|
Sign up to set email alerts
|

Brachial Plexus Neuropathies During the COVID-19 Pandemic: A Retrospective Case Series of 15 Patients in Critical Care

Abstract: Objective The utilization of the prone position to treat patients with COVID-19 pneumonia who are critically ill and mechanically ventilated is well documented. This case series reports the location, severity, and prevalence of focal peripheral nerve injuries involving the upper limb identified in an acute COVID-19 rehabilitation setting. The purpose of this study was to report observations and to explore the challenges in assessing these patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 19 publications
3
73
0
7
Order By: Relevance
“…Altogether, 105 articles about SARS-CoV-2-associated neuropathy describing 220 patients with Guillain-BarrĂ© syndrome (GBS) 4 and 41 patients with non-GBS neuropathy were retrieved 5,6,7,8,9,10,11,12,13,14 . The age of these 261 patients, reported in 244 of them, ranged from 8 to 94 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Altogether, 105 articles about SARS-CoV-2-associated neuropathy describing 220 patients with Guillain-BarrĂ© syndrome (GBS) 4 and 41 patients with non-GBS neuropathy were retrieved 5,6,7,8,9,10,11,12,13,14 . The age of these 261 patients, reported in 244 of them, ranged from 8 to 94 years.…”
Section: Resultsmentioning
confidence: 99%
“…Drugs known to cause neuropathy and given to patients included daptomycin 15 , linezolid 16 , lopinavir 17 , ritonavir 18 , hydro-chloroquine 19 , cisatracurium 20 , clindamycin 21 , tocilizumab 22 , and glucocorticoids 23,24 . Compression neuropathy was diagnosed in 18 cases 9,10,14 . Nerve conduction studies (NCSs) showed axonal lesion in four patients 6 and plexopathy in one patient 10 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, there appears to be a predominance of frontal lobe EEG abnormalities in COVID-19, which has been raised as a potentially pathognomonic feature of encephalopathy in COVID-19; other described abnormalities, such as epileptiform discharges, are commonly the result of underlying or pre-existing neurological pathology [115]. Prolonged periods of immobility, and particularly the use of pronepositioning for the amelioration of refractory hypoxaemia are associated with compressive and traction neuropathies and plexopathies [50,116,117]. Common risk factors for the development of critical illness polyneuromyopathy, such a prolonged ventilation, systemic inflammatory response syndrome, acute respiratory distress syndrome and multiorgan failure [118] are all frequently seen in COVID-19 [63], leading to a high occurrence of this condition [119].…”
Section: Neurological Sequelae Of Critical Illnessmentioning
confidence: 99%
“…6 Pro-sensing biohybrids for the generation of accelerated antiviral immunity applicable to the first sensory interface between the host and SARS-CoV-2 associated proteins, myelin-associated glycoprotein, neurite outgrowth inhibitor (Nogo-A), oligodendrocyte/myelin glycoprotein, ephrins, chondroitin sulfate proteoglycans, and semaphorin 3A (Sema3A) along with activated microglia and macrophages and glial scar, and providing guidance cues to neural stem cells (NSC) by different mechanisms that contribute to the regulation of NSC differentiation [133]. COVID-19-associated nerve injuries mostly rooted in the ulnar nerve and the cords of the brachial plexus are presented by neuropathic pain and muscle wasting and affect the upper limb [134]. In addition to the effect of prolonged prone positioning [135] and related nerve compression injuries and vascular suppression and hematoma and related entrapment of the nerve(s) [136], neuroinflammation plays a role in nerve damages due to COVID-19.…”
Section: Conductive Biomaterials For Neural Regenerationmentioning
confidence: 99%